CSE—Comprehensive Sexuality Education: Urgensi dan Implementasinya pada Pembelajaran Sosiologi di SMA - Ratih Tyas Arini; Nasution; Sarmini (EDUKASIA Jurnal Pendidikan dan Pembelajaran, 2023)
The study aims to recognize the urgency of comprehensive sexuality education, the implementation of comprehensive sexuality education in the curriculum, and the integration of comprehensive sexuality education through sociological learning in schools. The study uses a qualitative approach with literary analysis techniques. The study used relevant literature from books and national and international journals related to material on CSE—Comprehensive Sexuality Education—and adolescent sexual behavior. The results of the analysis showed that comprehensive sexuality education gives adolescents the strength to exercise their rights, avoid unplanned pregnancies, build relationships that respect each other, and value equality, respect, consent, and diversity. It also helps address issues such as violence against women and girls and patriarchal dominance. Comprehensive sexuality education can be integrated with sociological learning in schools to examine topics related to sexuality, gender discrimination, consent, stereotypes, and gender-based violence. Schools need to implement it through curricula and equip teachers with training, involving parents and the community. The implications of this study are to provide an understanding of the importance of comprehensive sexual education to policymakers and the general public in order to minimize the negative impact of pre-sexual behavior on adolescents